Novel loci controlling lymphocyte proliferative response to cytokines and their clustering with loci controlling autoimmune reactions, macrophage function and lung tumor susceptibility - Lipoldová, Marie; Havelková, Helena; Badalová, Jana; Demant, Peter (International journal of cancer, 2005)
Novel genotyping and statistical tools have led to mapping of numerous QTL loci for multigenic traits that previously could not be detected. The relationships of these QTL families to other QTL families and the functional specialization of their members can now be studied. We have mapped a number of loci controlling activation of T lymphocytes by mitogens and cytokines and their capacity to produce cytokines. In (O20xOcB-9)F2 hybrids, we mapped 3 novel loci controlling proliferative T-cell response to cytokines IL-2 and IL-4 (Cinda3) or IL-4 only (Cinda4 and Cinda5). OcB-9 allele at Cinda3 controls a higher response than the O20 allele to both IL-2 and IL-4, and OcB-9 alleles of Cinda4 and Cinda5 control higher response to IL-4. These novel Cinda loci and the previously mapped Cinda1 locus seem to be located in genomic regions together with other QTL families: macrophage function loci Marif1 and Marif2, proteoglycan-induced arthritis loci Pgia4, Pgia7 and Pgia12 and lung tumor susceptibility loci Sluc1, Sluc4, Sluc6 and Sluc20. The possible relevance of these QTL associations in several different sites of the genome for the immune response, inflammation and tumorigenesis has to be elucidated.
Keywords: nádorová transformace buněk; Male; Genetic Predisposition to Disease; Inflammation; nádory plic; Cell Proliferation; Genotype; Lung Neoplasms; cytokiny; Autoimmunity; Cell Transformation, Neoplastic; mužské pohlaví; lymfocyty; zánět; lokus kvantitativního znaku; autoimunita; genom; Animals; ženské pohlaví; Quantitative Trait Loci; Lymphocytes; zvířata; makrofágy; myši; proliferace buněk; genotyp; Cytokines; Genome; Mice; Female; Macrophages; genetická predispozice k nemoci